Multi-criteria for Selection of SmartPhone Brands Product using AHP-TOPSIS Method - Akmaludin, Akmaludin; Badrul, Mohammad (Politeknik Ganesha Medan, 2019)
Today's communication is very important to do, this can be done by using communication tools that are currently being used by everyone, none other than SmartPhone, so people are competing to get it. Many found difficulties in choosing a SmartPhone Brand Product that suits the wishes of each user from a number of alternatives such as Advance, Xiaomi, OPPO, SAMSUNG, and VIVO, because many criteria must be considered such as memory capacity, battery durability, sharpness of capture camera, the form of design producy, the number of features produced from the product, which is equally important is the overall performance of the product. This difficulty is a general matter discussed by each user, because it requires the best solution that can be used to solve the problem. One method that can be used to select the right SmartPhone is the Analytic Hierarchy Process (AHP) method combined with the TOPSIS method. In this case AHP is used to determine the preference quantity in weighting and TOPSIS is used for mathematical detailed calculations of a number of criteria specified in ranking from a number of alternatives. The results obtained based on the mathematical calculation process are the first rank brand products with the highest weight of 0.597 from SAMSUNG, followed by a weight of 0.586 from OPPO, then weighing 0.555 from Advance, then weighing 0.511 from VIVO, and the smallest weight 0.491 from Xiaomi.